Are Parents Really Partners in Their Child’s Education? - Rosas, Clarissa E.; Winterman, Kathleen G. (Journal of the American Academy of Special Education Professionals, 2014)
Although federal legislation requires parent involvement in the development of Individualized Education Programs, parents often lack adequate background knowledge to partner with school personnel in the development of programs for their child. In an effort to provide all stakeholders with information pertaining to the education of children with disabilities, state departments of education publish documents on policies and procedures concerning special education services. This study examined the readability level of those published documents to determine if they were commensurate with the reading level of most adults. Results of this study indicate that at the surface level, the documents appear to be written at a level of understandability that most adults should comprehend. However, upon further examination, it was revealed that the level of literacy proficiency required to interpret the documents requires a more sophisticated level of literacy. Therefore the documents are not commensurate with the literacy level of most adults.